The Mind of a Poet A Study of Wordsworth's Thought with Particular Reference to "The Prelude" - Havens, Raymond Dexter (Johns Hopkins University Press, 2020)
Originally published in 1941. This book stresses the transcendental, rather than purely aesthetic, qualities of William Wordsworth's work. It argues that the unusual aspects of Wordsworth's mind are not isolated and did not seem to him fanciful or merely personal; they were, for him, so many paths, difficult to find and harder to follow, yet leading to the great central truth that is the goal of all humankind's loftier strivings.